2011
DOI: 10.5603/fhc.2011.0016
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HOXA-10 and HOXA-11 in the endometria of women with idiopathic infertility

Abstract: Abstract:In fertile women, HOXA-10 and HOXA-11 expression rises during the luteal phase, with the peak occurring during the implantation window, and stays at a high level until the end of the cycle. We evaluated the transcript and protein levels of HOXA-10 and HOXA-11 in the endometria of patients with idiopathic infertility (n = 15) and control patients (n = 10). The amounts of mRNA were determined by reverse transcription and real-time quantitative PCR. The protein levels were evaluated by Western blotting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
(36 reference statements)
1
16
1
6
Order By: Relevance
“…Decidualization is the process whereby endometrial stromal cells transform into specialized secretory decidual cells that provide a nutritive and immunoprivileged matrix essential for embryo implantation and placental development [32]. HOXA10 is a well-known molecule involved in the mechanism of implantation, and a decrease of implantation rates has been observed in women with altered HOXA10 expression [33]. Indeed, HOXA10 expression reaches a peak during the window of implantation in response to estrogen and progesterone.…”
Section: Vitamin D and Normal Endometriummentioning
confidence: 99%
“…Decidualization is the process whereby endometrial stromal cells transform into specialized secretory decidual cells that provide a nutritive and immunoprivileged matrix essential for embryo implantation and placental development [32]. HOXA10 is a well-known molecule involved in the mechanism of implantation, and a decrease of implantation rates has been observed in women with altered HOXA10 expression [33]. Indeed, HOXA10 expression reaches a peak during the window of implantation in response to estrogen and progesterone.…”
Section: Vitamin D and Normal Endometriummentioning
confidence: 99%
“…These genes usually bind to the regulatory regions of their downstream target genes involved in endometrial development and regulate their transcriptional expression [5]. Altered expression of HOX genes are reported to be associated with a number of infertility related disorders with decreased rate of implantation including PCOS, idiopathic infertility, endometriosis and recurrent spontaneous miscarriage [4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, histology alone cannot effectively assess endometrial receptivity; molecular evaluation of the endometrium is a potential means of identifying defects in receptivity. Alterations in endometrial expression of some genes have been identified in several clinical conditions associated with impaired endometrial receptivity: endometriosis, idiopathic infertility and hydrosalpinges (Alizadeh et al, 2011;Szczepańska et al, 2011;Bildirici et al, 2001). In this study, the effect of myomas on the endometrium was evaluated using several established molecular markers of endometrial receptivity: HOXA11, LIF as well as BTEB1.Homeobox (Hox/HOX) genes encode transcription factors that mediate embryonic development.…”
Section: Resultsmentioning
confidence: 99%